Moving Beyond Sisyphus in Agriculture R&D to Be Climate Smart and Not Gender Blind - Anderson, Simon; Sriram, Vidhya (Frontiers in Sustainable Food Systems, 2019)
Gender differentiation in smallholder farming and agriculture and the need to ‘feminize’ agricultural development have been recognised as critical to poverty reduction. Evidence now demonstrates that the shocks resulting from climate risks to agriculture and food security and adaptive responses are highly gender-differentiated. However, agricultural research and development have not delivered the transformative changes needed in smallholder farming from a poverty eradication and gender equality perspective, and particularly to support women to adapt to climate risks. Climate smart agriculture represents a step change in the ways that issues related to crop and livestock productivity, the climate adaptive capacity of smallholder farming, and the carbon footprint of farming are investigated and technologies transferred. However, international agriculture research and development have struggled to find effective ways of integrating gender equitable outcomes in agriculture programmes. High level strategic decisions have not prioritised resources for gender equality work resulting in climate smart agriculture being rather gender blind. Knock on effects down the research and development strata have meant that some development agencies have taken up a CSA approach without addressing gender inequalities. While others, including some INGOs, are pushing for greater attention to gender equality in agricultural development. Methodological remedies that can enable gender equality to be better addressed through agricultural research and development have been identified from tool-boxes to epistemological change. But without a change in high level prioritisation of resources the potential for a climate smart and gender responsive international agriculture research and development remains out of reach.